Hadamard-type fractional differential equations, inclusions and inequalities. (2017) - (Mathematics professor), Ahmad, Bashir; Alsaedi, Ahmed; Ntouyas, Sotiris, 1950-; Tariboon, Jessada, 1975-
No abstract available